Phytochemistry and Pharmacology of Zanthoxylum gilletii: A Review - J. P. Mbula; E. M. Kitete; N. G. Kasiama; E. M. Ngoyi; J. T. K. Kwembe; D. D. Tshilanda; K. N. Ngbolua; D. S. T. Tshibangu; S. O. Mihigo; O. Onautshu; P. T. Mpiana (Archives of Current Research International, 2022)
Aim: Zanthoxylum gilletii is used in traditional medicine against several pains, namely urinary tract infections, malaria, lombargy, high blood pressure etc. Thus, the aim of this study was to review the literature on the traditionnal use, the phytochemical composition and the biological activities of the above-mentioned plant. Methodology: A literature review was conducted based on the scientific results sourced from Science Direct, PubMed, Google Scholar, SciLEO and PubMed Central. The plant scientific name was used as a search keyword together with the following words phytochemistry, pharmacology, bioactivity and pharmacognosia. Results: Z. gilletii extracts have shown antimicrobial, antifungal, antiparasitic and anticancer activities. Several compounds have been reported from different parts of the plant including alkaloids, amides, coumarins and essential oils and have shown interesting biological properties such as the antioxidant and antimicrobial activities. However, there are, to date, several compounds whose biological activities are not known, especially that belonging to the essential oil class. At the same time, there are also the activities observed but for which the responsible compounds are unknown. Conclusion: All parts of Z.gilletii are used in traditional medicine and decoction is the most recommended method of preparation. Data from phytochemical studies are quite poor, especially on essential oils.